Spontaneous Massive Splenic Infarction in the Setting of Renal Transplant and Septic Shock: A Case Report and Review of the Literature - Christine L. Bokman; Maroun Sfeir; Veer Chahwala; Enrique Ginzburg (Case Reports in Medicine)
Massive splenic infarction (MSI) is a rare phenomenon that results from compromised blood flow to more than half of the spleen. Causes of MSI include hematological disorders, coagulopathies, infection, and embolization, and, rarely, MSI is spontaneous. The mainstay of treatment is splenectomy. We report the case of a 50-year-old man with a history of renal transplant who presented with diffuse abdominal pain and rapidly developed septic shock. A computed tomographic study (CT scan) of the abdomen demonstrated MSI. The surgical team was consulted for splenectomy but conservative management was maintained and immune function preserved. The patient’s clinical condition was resolved over a three-week period. This report demonstrates successful nonoperative management of a spontaneous MSI most likely secondary to hypoperfusion and a hypercoagulable state from both septic shock and renal transplant.